Integrated analysis of genome-wide miRNAs and targeted gene expression in esophageal squamous cell carcinoma (ESCC) and relation to prognosis - Yang, Howard (BMC Cancer, 2020)
BACKGROUND: Esophageal squamous cell carcinoma (ESCC) is a leading cause of cancer death worldwide and in China. We know miRNAs influence gene expression in tumorigenesis, but it is unclear how miRNAs affect gene expression or influence survival at the genome-wide level in ESCC. METHODS: We performed miRNA and mRNA expression arrays in 113 ESCC cases with tumor/normal matched tissues to identify dysregulated miRNAs, to correlate miRNA and mRNA expressions, and to relate miRNA and mRNA expression changes to survival and clinical characteristics. RESULTS: Thirty-nine miRNAs were identified whose tumor/normal tissue expression ratios showed dysregulation (28 down- and 11 up-regulated by at least two-fold with P < 1.92E-04), including several not previously reported in ESCC (miR-885-5p, miR-140-3p, miR-708, miR-639, miR-596). Expressions of 16 miRNAs were highly correlated with expressions of 195 genes (P < 8.42E-09; absolute rho values 0.51–0.64). Increased expressions of miRNA in tumor tissue for both miR-30e* and miR-124 were associated with increased survival (P < 0.05). Similarly, nine probes in eight of 818 dysregulated genes had RNA expression levels that were nominally associated with survival, including NF1, ASXL1, HSPA4, TGOLN2, BAIAP2, EZH2, CHAF1A, SUPT7L. CONCLUSIONS: Our characterization and integrated analysis of genome-wide miRNA and gene expression in ESCC provides insights into the expression of miRNAs and their relation to regulation of RNA targets in ESCC tumorigenesis, and suggest opportunities for the future development of miRs and mRNAs as biomarkers for early detection, diagnosis, and prognosis in ESCC.